2020
DOI: 10.21203/rs.3.rs-40777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wdr47, Camsaps, and Katanin cooperate to generate ciliary central microtubules

Abstract: The axonemal central pair (CP) are non-centrosomal microtubules critical for planar ciliary beat. How they form, however, is poorly understood. Here, we show that mammalian CP formation requires cooperative activities of Katanin, Camsaps, and Wdr47. Katanin severs peripheral microtubules to produce central microtubule seeds in nascent cilia. Camsaps stabilize minus ends of the seeds to facilitate MT outgrowth, whereas Wdr47 concentrates Camsaps into the axonemal central lumen to properly position the central m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The easiest way to assess motile cilia function is by quantifying CBF via highspeed video microscopy (Francis & Lo, 2013;O'Callaghan et al, 2012;Sisson et al, 2003) and this forms a sizable chunk of the cilia literature. However, no standardized frame rate exists when imaging cilia motility for subsequent CBF calculation, this has resulted in a large range of frames rates used to image cilia motility within the published literature (Abdelhamed et al, 2018;Abdelhamed et al, 2020;Bustamante-Marin et al, 2019;Chen et al, 2016;Hagiwara et al, 2020;Hennessy et al, 1986;Liu et al, 2021; F I G U R E 3 Assessing how movie framerate influences CBF measurement accuracy for cilia beating between 0-15 Hz, as quantified by either manual counting or FFT-based algorithm (MATLAB). Cilia data from all tissues and temperatures that displayed reference CBFs between 0-15 Hz was pooled (n = 73) (reference CBF was calculated from 300 fps movies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The easiest way to assess motile cilia function is by quantifying CBF via highspeed video microscopy (Francis & Lo, 2013;O'Callaghan et al, 2012;Sisson et al, 2003) and this forms a sizable chunk of the cilia literature. However, no standardized frame rate exists when imaging cilia motility for subsequent CBF calculation, this has resulted in a large range of frames rates used to image cilia motility within the published literature (Abdelhamed et al, 2018;Abdelhamed et al, 2020;Bustamante-Marin et al, 2019;Chen et al, 2016;Hagiwara et al, 2020;Hennessy et al, 1986;Liu et al, 2021; F I G U R E 3 Assessing how movie framerate influences CBF measurement accuracy for cilia beating between 0-15 Hz, as quantified by either manual counting or FFT-based algorithm (MATLAB). Cilia data from all tissues and temperatures that displayed reference CBFs between 0-15 Hz was pooled (n = 73) (reference CBF was calculated from 300 fps movies).…”
Section: Discussionmentioning
confidence: 99%
“…Our data matches previously published findings by highlighting the significant difference in CBF between airway and ependymal cilia and by emphasizing how CBF is modulated by changes in temperature. Murine ependymal cilia have been previously shown to beat significantly faster than airway cilia (Francis et al, 2009;Hagiwara et al, 2020;Mahuzier et al, 2018;Mikhailik et al, 2021), while increased incubation temperature is well recognized to result in a linear increase in mean CBF (Christopher et al, 2014;Schipor et al, 2006;Sisson et al, 2003;Welchering et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that WDR47/NMTN-1 ensures proper IFT particle movement and cargo delivery in the AWB neurons, promoting ciliogenesis. WDR47/NMTN-1 has been revealed as a microtubule-associated protein; it has been shown to interact with CAMSAP family proteins for microtubule-mediated processes (Chen, Zheng et al 2020, Buijs, Hummel et al 2021, Liu, Zheng et al 2021. In noncentrosomal microtubules, WDR47/NMTN-1 protects CAMSAP2 against kataninmediated severing and is required for axonal and dendritic development (Buijs, Hummel et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In noncentrosomal microtubules, WDR47/NMTN-1 protects CAMSAP2 against kataninmediated severing and is required for axonal and dendritic development (Buijs, Hummel et al 2021). In mammalian multicilia, WDR47/NMTN-1 co-operates with CAMSAP family proteins and MT-severing enzyme katanin to generate ciliary central microtubules (Liu, Zheng et al 2021). WDR47/NMTN-1 also functions through CAMSAP3 to control neuronal migration and the early stages of neuronal polarization, which is important for neonatal mouse survival (Chen, Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation